TDHF and a Macroscopic Aspect of Low-Energy Nuclear Reactions - Washiyama, Kouhei; Sekizawa, Kazuyuki (Frontiers in Physics, 2020)
Time-dependent Hartree–Fock (TDHF) method has been applied to various low-energy nuclear reactions, such as fusion, fission, and multinucleon transfer reactions. In this Mini Review, we summarize recent attempts to bridge a microscopic nuclear reaction theory, TDHF, and a macroscopic aspect of nuclear reactions through nucleus–nucleus potentials and energy dissipation from macroscopic degrees of freedom to microscopic ones obtained from TDHF in various colliding systems from light to heavy mass regions.